Researching Media in the Digital Performance: Methods and Techniques - Babatunde Covenant Olugbenga; Muhammad Ridwan (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2025)
The intersection of media and performance has undergone a profound transformation in the digital age, giving rise to new paradigms of creation, dissemination, and audience engagement. This paper explores the methodologies and techniques used to research media within the context of digital performance, a field that merges traditional performance practices with digital technologies such as virtual reality, augmented reality, live streaming, and interactive media. Through a critical examination of qualitative and practice-based research methods including ethnography, digital ethnography, performance analysis, and creative practice as research this study maps the evolving landscape of media in digital performance. It also addresses key challenges such as ephemerality, interactivity, and technological mediation. The aim is to provide a comprehensive framework for scholars and practitioners to navigate and interrogate this rapidly evolving field, contributing to the broader discourse on digital humanities, media studies, and performance theory.